Thinking styles and time perspectives. Issue 1 (2nd January 2022) - Kuan, Tat-Yeung James; Zhang, Li-Fang
Abstract: The principal objective of this research was to examine the relationships between thinking styles and time perspectives. Four hundred and fifty-one secondary school students from Hong Kong responded to the Thinking Styles Inventory-Revised II (TSI-R2) and the Zimbardo Time Perspective Inventory (ZTPI). Results showed that when gender, school year level, and age were taken into account, thinking styles significantly predicted time perspectives. Students possessing successful thinking styles (i.e. using a wide range of thinking styles, especially creativity-generating styles) tended to have the more desirable time perspectives. The optimal profile of a balanced time perspective was predicted positively by the hierarchical and external styles. Implications of the findings for secondary school students and educators are discussed.